The influence of subliminal crosstalk in dementia narratives. (July 2019) - Chatwin, John; Capstick, Andrea
Ethnographic audio-visual research data recorded in a busy dementia care environment were initially considered to be 'contaminated' by unwanted background noise. This included a variety of elements: ambient sound, mechanical noise, non-narrative vocalisation and narrative fragments from parallel conversation. Using the methodological lens of conversation analysis, we present an exploration of the striking temporal and sequential resonances between the narrative of one man with dementia and a group of care staff holding a separate conversation some distance away. We suggest that in this and similar settings, where random and intrusive background sounds and conversation form a ubiquitous backdrop, the presence of such 'noise' can have a detectable influence on the content and direction of situated narratives. We argue that rather than attempting to filter out these apparently intrusive sounds from micro-interactional data, interference elements can usefully be incorporated into the analysis of interactions.